Adeno-associated virus vectors for retinal gene therapy in basic research and clinical studies - Xia, Xue; Guo, Xinzheng (Frontiers in Medicine, 2023)
Retinal degenerative diseases, including glaucoma, age-related macular degeneration, diabetic retinopathy, and a broad range of inherited retinal diseases, are leading causes of irreversible vision loss and blindness. Gene therapy is a promising and fast-growing strategy to treat both monogenic and multifactorial retinal disorders. Vectors for gene delivery are crucial for efficient and specific transfer of therapeutic gene(s) into target cells. AAV vectors are ideal for retinal gene therapy due to their inherent advantages in safety, gene expression stability, and amenability for directional engineering. The eye is a highly compartmentalized organ composed of multiple disease-related cell types. To determine a suitable AAV vector for a specific cell type, the route of administration and choice of AAV variant must be considered together. Here, we provide a brief overview of AAV vectors for gene transfer into important ocular cell types, including retinal pigment epithelium cells, photoreceptors, retinal ganglion cells, Müller glial cells, ciliary epithelial cells, trabecular meshwork cells, vascular endothelial cells, and pericytes, via distinct injection methods. By listing suitable AAV vectors in basic research and (pre)clinical studies, we aim to highlight the progress and unmet needs of AAV vectors in retinal gene therapy.